2014
DOI: 10.1016/j.ecss.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters of tropical lesser noddies respond to local variations in oceanographic conditions and weather

Abstract: Keywords:breeding phenology chick mass gain chlorophyll-a fledging success Indian Ocean dipole mode ocean primary productivity sea surface temperature Regional terms:Western Indian Ocean Seychelles Anous tenuirostris a b s t r a c t Most attempts to link seabirds and climate/oceanographic effects have concerned the Atlantic and Pacific Oceans with comparatively few studies in the tropical Indian Ocean. This paper examines the reproductive response of the lesser noddy Anous tenuirostris to temporal fluctuations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…In only one species (northern gannet) was breeding success predicted to increase under the future climate scenario. Our results build upon previous findings that have demonstrated the importance of climate on breeding success and other vital rates in seabirds globally, but which have tended to focus on single breeding colonies or species (Jones et al 2007, Barbraud et al 2011, Jenouvrier et al 2014, Monticelli et al 2014, Carroll et al 2015, Christensen-Dalsgaard et al 2018; but see Sydeman et al 2021) or on abundance, not vital rates (Johnson et al 2013). Very few studies have estimated future vital rates for seabirds under projected future climates (but see Carroll et al 2015) or across broad regions such as the North Sea (but see recent review by Pearce-Higgins 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In only one species (northern gannet) was breeding success predicted to increase under the future climate scenario. Our results build upon previous findings that have demonstrated the importance of climate on breeding success and other vital rates in seabirds globally, but which have tended to focus on single breeding colonies or species (Jones et al 2007, Barbraud et al 2011, Jenouvrier et al 2014, Monticelli et al 2014, Carroll et al 2015, Christensen-Dalsgaard et al 2018; but see Sydeman et al 2021) or on abundance, not vital rates (Johnson et al 2013). Very few studies have estimated future vital rates for seabirds under projected future climates (but see Carroll et al 2015) or across broad regions such as the North Sea (but see recent review by Pearce-Higgins 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have identified relationships between seabird breeding success and climate variables including terrestrial temperature and precipitation (Smith & Gaston 2012, Watanuki & Ito 2012, Christensen-Dalsgaard et al 2018, Michielsen et al 2019 as well as marine climate variables including spring North Atlantic Oscillation (NAO), winter NAO, sea surface temperature (SST) and sea surface salinity (SLM) (Jones et al 2007, Watanuki & Ito 2012, Monticelli et al 2014, Carroll et al 2015. Terrestrial winter temperature and rainfall have been linked to survival in seabirds, thought to be driven by physiological stress arising from more extreme weather conditions, such as cooler and wetter phases increasing exposure risk (Smith & Gaston 2012) as well as high terrestrial temperatures during breeding causing heat stress (Smith & Gaston 2012, Michielsen et al 2019.…”
Section: Data On Climate and Other Environmental Characteristicsmentioning
confidence: 99%
“…Local SSTA represent a different spatial scale and thus reflect environmental conditions close to the colony. All three variables have previously shown to affect either breeding biology or population dynamics of other seabird species, including (rockhopper) penguins [ 54 60 ].…”
Section: Methodsmentioning
confidence: 99%